Incidencia de la depresión en las relaciones interpersonales en un adolescente de 17 años de la ciudad de Babahoyo - Castillo Salvatierra, Gladys Patricia (2023)
This case study was conducted in order to know, diagnose, analyze and apply treatment about the prevalence of depressive disorders in an adolescent from the city of Babahoyo and to elucidate the effect of its development on interpersonal relationships in their psychosocial environment, with a view to improving the quality of life of the patient and his social environment. The research was carried out through the application of qualitative and descriptive methods, using psychological methods and tools, such as clinical observation, which allowed us to analyze the symptoms; semi-structured clinical interview, which allowed us to obtain relevant information on the patient; The first step was the detection of a case of depression in a 17-year-old adolescent in 2022 in the city of Babahoyo, Ecuador, followed by a review of the clinical history; from the analysis of the case, sessions were planned to correct the disorder evaluated for the improvement of the patient and the acquisition of knowledge and attitudes that would allow him to incorporate into his social environment normally. In the treatment, CBT model was applied in which the following techniques were used: scheduling of activities to be carried out by the patient including schedules, the use of pleasant activities, emotional techniques that seek to reduce the patient's negative emotional state through management strategies, techniques of grade mastery and scheduling of activities, to achieve the recovery of the patient's emotional state.